MANAJEMEN PROGAM PENUMBUHAN BUDI PEKERTI PESERTA DIDIK DI SD BAKULAN JETIS BANTUL - Nunung Nurhayani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2018)
This study aimed to describe the implementation of the program management which included planning, organizing, actuating, and monitoring the obstacles. This study was a qualitative study conducted at SD Bakulan located in Jetis, Bantul, DIY. The data collection techniques in this study were observation, interview, and documentation. The technique of data analysis applied the interactive analysis model by Miles and Huberman with steps of data collection, data reduction, and data verification or conclusion. Mechanical checks for the validity of the data used an extension of observation, stable observation, and triangulation data. The result of the study showed that the development of the program management was well done. The implementation of the planning program has implemented on the annual work plan, work planning and school budgeting. The school curriculum through the self-development program was integrated into the school activity, in a routine, spontaneous, exemplary, and conditioning teaching and learning activities. The school culture which was arranged by the headmaster in order to maximize all of the school’s potential both of the human resources as well as the infrastructure to achieve the school’s objective. The actuating was done by the teachers, students, the employees integratively and was planned to conduct the program through the socialization to the parents meeting, student enrollment, ceremony, official meeting, and school’s briefing. It was also done through the self- development program integrated to the school’s activity, routine, spontaneous, exemplary, conditioning, teaching and learning activities, and school’s culture. The supervising was done by the headmaster, classroom teacher, sports teachers, and religion teacher. The direct supervision by the headmaster conducted through the routine coordination after the ceremony on Monday and learning supervision. The obstacles that were faced on the implementation of the program was related with the particular situation such as the construction of new building, the advancement of the information technologies, and the lack of book collection in the library for the literacy activity so that several programs that had been planned could not be conducted. Meanwhile, the supporting factors of the program were solidarity, the synergy of the stakeholder, the rural environment, and adequate infrastructure.